2022
DOI: 10.3390/biomedicines10081967
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Vascular Abnormalities in the Aging 3xTg-AD Mouse Model of Alzheimer’s Disease

Abstract: Vascular dysfunction and structural abnormalities in Alzheimer’s disease (AD) are known to contribute to the progression of the pathology, and studies have tended to ignore the role of the vasculature in AD progression. We utilized the 3xTg-AD mouse model of AD to examine individual cerebral vessels and the cortical vascular network across the lifespan. Our vessel painting approach was used to label the entire cortical vasculature, followed by epifluorescence microscopy. The middle cerebral artery (MCA) tree w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“… Giuliani et al (2019) reported that cortical microvessel density, as evaluated by laminin immunostaining on coronal slices, was higher in 5-month-old Tg2576 mice, compared with age-matched WT, but was lower at 27 months in Tg2576 mice. We also reported an overall increase in vascular density with age in the 3xTg-AD mouse model using vessel painting ( Jullienne et al, 2022a ). Thus, across the cortex of WT and 5xFAD mice we find a generalized increase in vascular features, which appears to be independent of genotype when both sexes are combined.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“… Giuliani et al (2019) reported that cortical microvessel density, as evaluated by laminin immunostaining on coronal slices, was higher in 5-month-old Tg2576 mice, compared with age-matched WT, but was lower at 27 months in Tg2576 mice. We also reported an overall increase in vascular density with age in the 3xTg-AD mouse model using vessel painting ( Jullienne et al, 2022a ). Thus, across the cortex of WT and 5xFAD mice we find a generalized increase in vascular features, which appears to be independent of genotype when both sexes are combined.…”
Section: Discussionmentioning
confidence: 88%
“…All vascular analysis methods utilized in the current study have been previously published ( Salehi et al, 2018 ; Jullienne et al, 2022a ). Briefly, classical vessel analysis was performed using AngioTool Software ( RRID:SCR_016393 ) for measures of vessel density, length, and number of junctions ( Zudaire et al, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…Vascular dysfunction, in part due to hypertension and atherosclerosis, is an early feature of AD (Sweeney et al, 2019). Of note, there are progressive cerebrovascular abnormalities in an AD mouse model (Jullienne et al, 2022).…”
Section: Hypertension and Cardiovascular Diseasementioning
confidence: 99%
“…Microgliosis and astrocyte activation are evident by 7 months of age. [57] Microvascular damage has been reported to precede plaque formation at 3-months [58,59]. Neurovascular uncoupling has been reported in 1-month-old transgenic mice associated with decreased NO production [60].…”
Section: Xtg Mouse Modelmentioning
confidence: 99%